Cover Feature: Catalyst Development for the Synthesis of Ozonides and Tetraoxanes Under Heterogeneous Conditions: Disclosure of an Unprecedented Class of Fungicides for Agricultural Application (Chem. Eur. J. 21/2020). Issue 21 (8th April 2020) - Yaremenko, Ivan A.; Radulov, Peter S.; Belyakova, Yulia Y.; Demina, Arina A.; Fomenkov, Dmitriy I.; Barsukov, Denis V.; Subbotina, Irina R.; Fleury, Fabrice; Terent'ev, Alexander O.
Abstract : A catalyst for the synthesis of ozonides and tetraoxanes under heterogeneous conditions was developed. This work reports an unprecedented class of fungicides with significant potential for agricultural applications. More information can be found in the Full Paper by A. O. Terent'ev et al. on page 4734 .